(untitled) (Journal of the College of Basic Education, 2026)
The study aimed to find out the level of moral thinking among kindergarten teachers in the General Directorate of Education of Baghdad / Rusafa, and whether there are differences in the level of moral intelligence according to the two variables (educational qualification and years of service). The sample of the study consisted of (100) public kindergarten teachers. The researcher adopted the descriptive approach. To achieve the goal of the research, a measure of moral intelligence was prepared by the researcher, which included (45) items in its final form. The researcher verified the standard psychometric characteristics of the tool. I reached the following results: Kindergarten teachers have moral intelligence, and the results also showed that the educational qualification and years of service have no relationship to the moral intelligence of kindergarten teachers.